Visual Branding Band Ethereal di Kota Padang - Yani Trullya; Aditya Hanum Widarsa (Lembaga Pengembangan Kinerja Dosen, 2024)
Ethereal is a band that plays post black metal music in the city of Padang. However, the lack of introduction in the form of visual media to the Ethereal band causes few underground music lovers to know the identity of the Ethereal band. This design is carried out in order to increase the existence of the post black metal genre in Padang city and optimize and provide consistency to the introduction of the Ethereal band's identity so that it can be better known and remembered by the target audience. This design uses the Design Thingking method, so it can be concluded that in this design a problem is sourced to an empathy, the need for solutions to existing problems, then keep testing for improvement. Therefore, a manual book was made as the main media to introduce the Ethereal band to the target audience. By using data analysis called SWOT (strenghts, weaknesses, opportunities, threats). and supported by various supporting media on the visual branding of the Ethereal band in the form of: Digital Catalog, Poster, Ticket, T-shirt, Tumblr, Emblem, and Sticker Pack.